Fulvic acid exhibits antitumor effects in ovarian cancer cells by upregulating cytochrome P450 family 1 subfamily A member 1 expression - Min Chen; Ming Cheng; Chenchen Shao; Wenwen Liang; Yi Tang; Fangjun Ding (Discover Oncology)
Abstract Objective Fulvic acid (FA), a humic substance, has various applications in agricultural (animal husbandry) and pharmaceutical industries. However, to the best of our knowledge, its antitumor effects remain unclear. This study aimed to elucidate the effects and underlying mechanisms of FA in ovarian cancer cells. Methods To determine the half-maximal inhibitory concentration (IC50) of FA, SK-OV-3 and OVCAR3 ovarian cancer cells were exposed to various concentrations of FA. The effects of FA and expression of cytochrome P450 family 1 subfamily A member 1 (CYP1A1) on cellular proliferation, migration, and invasion were evaluated using the Cell Counting Kit-8 and transwell assays for migration and invasion. Differentially expressed messenger ribonucleic acids (mRNAs) were identified via Illumina ribonucleic acid (RNA) sequencing and verified using fluorescent quantitative reverse transcription polymerase chain reaction (qRT-PCR). CYP1A1 protein levels were measured by western blotting. Results The IC50 values of FA for OVCAR3 and SK-OV-3 cells were 689.9 and 752.0 µg/ml, respectively. FA treatment suppressed cell proliferation, invasion, and migration. In FA-treated SK-OV-3 cells, 117 mRNAs were upregulated, and 342 mRNAs were downregulated, as identified by Illumina RNA sequencing. The qRT-PCR results revealed that FA upregulated CYP1A1 expression in both cell lines. CYP1A1 overexpression mimicked the effects of FA treatment on cell proliferation, invasion, and migration. Furthermore, CYP1A1 knockdown alleviated these effects induced by FA treatments. Conclusion FA suppressed cell proliferation, invasion, and migration and upregulated CYP1A1 expression in SK-OV-3 and OVCAR3 cells. Our results suggest that FA demonstrates antitumor effects in ovarian cancer cells through CYP1A1 regulation.